Kaitan Aspek Non-Fisik Terhadap Pola Hunian di Desa Bali Aga : Desa Sukawana, Kabupaten Bangli - Ni Luh Putu Listyadewi Yurika (Jurnal Arsitektur ARCADE, 2025)
Abstract:Sukawana Village is one of the Bali Aga villages located in the highland area of Kintamani District, Bangli Regency, Bali. This village possesses distinctive characteristics that set it apart from other villages in Bali. Its uniqueness is reflected in various non-physical aspects, encompassing economic, social, and cultural dimensions, which are rooted in traditional concepts such as Ulu-Apad, Tri Hita Karana, and Kiwa-Tengen. These non-physical values are derived from a belief system inherited from the ancestors of the local community and are still upheld today. Such non-physical conditions significantly influence the settlement patterns and yard arrangements within the traditional village of Sukawana. This study aims to examine the correlation between non-physical aspects—including economic, social, and cultural factors—and the residential patterns in Sukawana Village. The research adopts a qualitative descriptive approach, employing primary data collection methods such as observation, interviews, and documentation, along with secondary data obtained through literature studies. The findings reveal a strong relationship between economic and socio-cultural aspects and the community's settlement patterns, particularly through the implementation of the concepts of Ulu-Apad, Hulu-Teben, Kiwa-Tengen, and Tri Hita Karana, which are deeply embedded in the spatial organization of homes and yards in Sukawana Village. Keyword : Non-Physical Aspects, Occupancy Patterns, Conception, Sukawana Village Abstrak: Desa Sukawana merupakan salah satu Desa Bali aga yang berada di daerah dataran tinggi di Kecamatan Kintamani, Kabupaten Bangli, Bali. Desa ini memiliki keunikan yang membedakannya dengan desa lain yang ada di Bali. Keunikannya dapat dilihat dari aspek non fisik yang mencakup aspek ekonomi, aspek sosial dan budaya yang berlandaskan konsepsi Ulu-Upad, Tri Hita Karana, dan Kiwa-Tengen. Nilai-nilai dari aspek non fisik tersebut didasari oleh sistem kepercayaan yang telah diwarisi oleh para leluhur masyarakat desa setempat yang hingga kini masih dijalankan. Kondisi aspek non-fisik tersebut yang tentunya mempengaruhi pola hunian atau pekarangan di Desa Adat Sukawana. Penelitian ini bertujuan untuk mengetahui keterkaitan dari aspek non-fisik yang meliputi aspek ekonomi, sosial dan budaya terhadap pola hunian di Desa Sukawana. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode pengumpulan data primer melalui observasi, wawancara, dan dokumentasi serta data sekunder dengan studi literatur. Hasil studi menunjukan bahwa adanya keterkaitan antara aspek ekonomi dan sosial budaya terhadap pola hunian masyarakat dengan adanya penerapan konsepsi Ulu-Apad, Hulu-Teben, Kiwa-Tengen serta Tri Hita Karana yang diimplementasikan terhadap pola hunian dan pekarangan masyarakat Desa Sukawana. Kata Kunci:   Aspek Non-Fisik, Pola Hunian, Konsepsi, Desa Sukawana